Peningkatan Pengetahuan Santriwan dan Santriwati TPQ Masjid Mashitoh Ngringo Palur Dengan Penyuluhan Kesehatan Mengenai Manajemen Pembuangan Sampah Yang Baik - Liss Dyah Dewi Arini; Saryadi Saryadi; Musta’in Musta’in (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Knowledge regarding good waste disposal management for Santriawan and Santriwati TPQ Mashitoh Ngringo Palur Mosque is still limited. It is important to provide knowledge about waste disposal management as an effort to equip oneself to maintain personal health. Good waste disposal management is an activity that aims to understand the meaning of waste, the characteristics of waste in the environment, waste management, good and correct waste management planning in the environment. Apart from that, it is hoped that students will increase awareness of the dangers that can arise due to not throwing rubbish in the right place. It is hoped that similar activities can have an impact on increasing awareness of the Indonesian people, especially students and female students as the younger generation, to actively participate in maintaining a clean and healthy environment. On this occasion, the Community Service Implementer for the D3 Medical Records and Health Information Study Program, Faculty of Health Sciences, Duta Bangsa University, Surakarta, will carry out P2M activities for the students of TPQ Mashitoh Ngringo, Palur regarding good waste disposal management. On this occasion, the Community Service implementer expressed his thanks to the head of TPQ Mashitoh Ngringo, Palur Karanganyar, who had given permission for a place to carry out Community Service activities. This activity provides benefits in increasing the knowledge of TPQ Mashitoh Ngringo, Palur Karanganyar female students regarding good waste disposal management with the hope that their knowledge regarding the meaning of waste, characteristics of waste in the environment, waste management, good and correct waste management planning in the environment. Apart from that, there is also an increase in awareness among female students of the dangers that can arise due to not throwing rubbish in the right place.